Transformation of Post Industrial Areas Into Public Open and Green Spaces; Ankara Maltepe Gasworks Example - Onur, Aksoy; Dilman, Merve; Atanur, Gül Sayan (My University, 2025)
Transforming post-ındustrial areas into public spaces is a common practice in urban areas. Maltepe Gasworks in Ankara, Türkiye, was selected for this study. The research aims to develop a new landscape design that enhances the area’s ecological, historical, and economic assets. In this context, the study consists of four stages. In the first stage, literature research was conducted. In the second stage, a SWOT analysis was carried out. Later, a new industrial landscape design proposal was developed for the region, taking into account ecological, historical and economic considerations. Finally, the current situation of the area and the new landscape design are compared. The SWOT analysis and neighborhood analysis used in the study revealed that the region lacks a historical identity and a green connection. With the new landscape design proposed for the area, a landscape design that takes into account ecological, historical identity and economic parameters has been developed. With the study, the area's historical identity, ecological and economic value have been allocated. In addition, the amount of green space is increased and the relationship between other green spaces is further strengthened with the proposed industrial landscape design.
Keywords: Dustrial area; public open green sphere; historical identity; ecological restoration; economic function